2016
DOI: 10.1038/srep21042
|View full text |Cite
|
Sign up to set email alerts
|

Role of C–N Configurations in the Photoluminescence of Graphene Quantum Dots Synthesized by a Hydrothermal Route

Abstract: Graphene quantum dots (GQDs) containing N atoms were successfully synthesized using a facile, inexpensive, and environmentally friendly hydrothermal reaction of urea and citric acid, and the effect of the GQDs’ C–N configurations on their photoluminescence (PL) properties were investigated. High-resolution transmission electron microscopy (HR-TEM) images confirmed that the dots were spherical, with an average diameter of 2.17 nm. X-ray photoelectron spectroscopy (XPS) analysis indicated that the C–N configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
161
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(178 citation statements)
references
References 49 publications
16
161
0
1
Order By: Relevance
“…p* and 1s ? r* transitions, respectively, shows typical spectra of graphitic carbon materials [37]. In addition, the C K-edge appeared in EELS of TiO 2 in Fig.…”
Section: Characterization Of Rgo-tio 2 Photoanodementioning
confidence: 88%
“…p* and 1s ? r* transitions, respectively, shows typical spectra of graphitic carbon materials [37]. In addition, the C K-edge appeared in EELS of TiO 2 in Fig.…”
Section: Characterization Of Rgo-tio 2 Photoanodementioning
confidence: 88%
“…The absence of bismuth or any other metal ion peak in the 12 h treated GQDs shows that the as-synthesized GQDs were free from the oxidants used to break it down. [49][50][51][52] The O1s spectrum showed a broad peak at the binding energy of ~532 eV which may be due to C=O and C-O bonds (Figure 2c). In N1s spectrum, two peaks were observed at ~401 eV and ~406 eV.…”
Section: Chemical Analysis Of As-synthesized Gqdsmentioning
confidence: 99%
“…Here, we have reported a one-step, low-cost, aqueous-phase, simple approach for the complete conversion of multiwalled carbon nanotubes into the water-dispersible GQDs with an average size ~3 nm using sodium bismuthate (NaBiO 3 ) as a strong oxidant. [49][50][51][52] The O1s spectrum showed a broad peak at the binding energy of ~532 eV which may be due to C=O and C-O bonds (Figure 2c). The cytotoxicity studies of GQDs against mammalian NIH 3T3 (mouse embryo fibroblast cells) and HEK 293T (human embryonic kidney cells) cells showed that the as-synthesized GQDs were non-cytotoxic up to the concentration of ~200 µg mL -1 .…”
mentioning
confidence: 99%
“…These spectra included a C–C, C=C peak with a binding energy of ~284 eV [Fig. 3(b);] 3941 which is observed in collagen spectra. 42 The atomic structure of collagen (that is, the material of our bioscaffolds) was confirmed with its three characteristic footprint signatures at 1630 cm −1 (corresponding to the amide I due to carbonyl stretching—C–H), 1551 cm −1 (corresponding to the amide II due to vibrations on the plane of the N–H bond and C–N stretching) and 1232 cm −1 (corresponding to vibrations on the plane of amide III due to C–N stretching and N–H deformation).…”
Section: Resultsmentioning
confidence: 99%